PENINGKATAN INFRASTRUKTUR TAMBAHAN BUS RAPID TRANSIT LAYANG PADA TRAYEK KAPTEN TENDEAN – BLOK M – CILEDUK - Hosein, Zainal; Arifin, Julison; Pahala, Yosi (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
This study was aimed at analyzing the process of Bus Rapid Transit additional infrastructure to lessen the negative effect to the society of the Transjakarta overpass route Capt. Tendean – Blok M – Cileduk. The qualitative method was used in this study along with three steps of analysis which were stakeholder using novelty analysis, infrastructure needs using content analysis, and Delphi method. The stakeholders’ mapping was government, society, academician, and business people with the government as the critical player. On the other hand, the business people have the most effect and the society has greater interest. The lucky winner is the academician who has the most effect and the interest. There were 20 respondents through purposive sampling. Questions were structured using priorities of content analysis with Likert scale.